Study on the Effect of Universal Joint Additional Bending Moment on Automobile NVH Performance - Jinli Xu; Shijun Luo; Bing Jia; Duanying Chen (Jixie chuandong)
As an important component in the automobile drive system，the performance of drive shaft has influence on NVH performance of the whole vehicle. In order to improve the influence of drive shaft on NVH performance，a design scheme to replace the intermediate universal joint of the drive shaft with Birfield CV joint is proposed based on the transmission characteristics analysis of universal joint and Birfield CV joint. The exciting forces at the inter-mediate support of three universal joint for two kinds of the drive shaft are solved and analyzed respectively. Results show that， due to the stable additional bending moment，the Birfield CV joint can reduce the exciting force at the intermediate support as well as the body of the vehicle，thus the NVH performance of the whole vehicle is improved.